EXO1/P53/SREBP1 axis-regulated lipid metabolism promotes prostate cancer progression - Zefeng Wang; Zheng Chao; Qi Wang; Fan Zou; Tianbao Song; Lizhe Xu; Jinzhuo Ning; Fan Cheng (Journal of Translational Medicine, 2024)
Abstract Prostate cancer (PCa) is one of the most common malignant tumors affecting the male genitourinary system. However, there is currently a lack of effective treatments for patients with advanced prostate cancer, which significantly impacts men’s overall health. Exonuclease 1 (EXO1), a protein with mismatch repair and recombination functions, has been found to play a vital role in various diseases. In our study, we discovered that EXO1 acts as a novel biomarker of PCa, which promotes prostate cancer progression by regulating lipid metabolism reprogramming in prostate cancer cells. Mechanistically, EXO1 promotes the expression of SREBP1 by inhibiting the P53 signaling pathway. In summary, our findings suggest that EXO1 regulated intracellular lipid reprogramming through the P53/SREBP1 axis, thus promoting PCa progression. The result could potentially lead to new insights and therapeutic targets for diagnosing and treating PCa.